LITERATURE REVIEW : PENGARUH KONSUMSI KOPI TERHADAP KADAR KOLESTEROL PADA PENGKONSUMSI KOPI - Anjelia Krispila; Donna Novina Kahanjak; Dian Mutiasari (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Cholesterol is a complex problem for humans when LDL levels dominate causing heart disease and hypertension as a result of atherosclerosis. Prevalence in the United States adults has increased cholesterol levels > by 12%. Central Kalimantan cholesterol sufferers data reached 54.2%. Cholesterol 2/3 is produced by the liver while 1/3 is absorbed by the digestive system from the food consumed. Coffee does not contain cholesterol, but coffee contains cafestol and fat- soluble kahweol, often called diterpenes. The purpose of this review is to determine the effect of coffee on increasing cholesterol levels. This study uses a systematic review approach with the keywords coffee, cholesterol levels, and the effect of coffee consumption, with the PRISMA method. From the search results, obtained 14 journals discussing the effect of coffee consumption on cholesterol levels and how much coffee consumption can affect cholesterol levels, and the effect of coffee consumption on LDL levels. A total of 12 journals (85.2%) stated that there was a significant effect while 2 journals (14.2%) stated that there was no significant effect. As for the results of a literature review, it can be concluded that there is an effect of coffee consumption on cholesterol levels, the amount of coffee consumption that can affect cholesterol levels, and the effect of coffee on LDL levels